LEGISLATIVE RATIO OF SEMA NUMBER 3 OF 2023 IN GUARANTEEING SUBSTANTIVE JUSTICE IN DIVORCE CASES - Nadia Romadhon; Abdul Rachmad Budiono; Hanif Nur Widhiyanti (CV. RADJA PUBLIKA, 2025)
The high divorce rate in Indonesia, particularly within the religious courts, has drawn serious scrutiny in the practice of family law enforcement. The most dominant grounds for divorce, namely persistent disputes and arguments, are often presented with weak and subjective evidence, potentially creating legal uncertainty and injustice for certain parties, particularly women. To address this issue, the Supreme Court issued Supreme Court Circular Letter (SEMA) Number 3 of 2023, which tightens the requirements for granting a divorce petition on the grounds of persistent disputes, through a new formulation requiring two cumulative elements: first, proven inability to live in harmony between husband and wife, and second, a minimum of six months of separation of residence, unless domestic violence (DV) is proven. This study aims to examine the Ratio legis of the issuance of SEMA 3 of 2023 and its implications for the fulfillment of substantive justice in divorce cases in the Religious Courts. Using a normative juridical approach with qualitative analysis methods, this study examines related laws and regulations, legal literature, and theories of justice and legal certainty. The research findings indicate that SEMA 3 of 2023 plays a significant role in normatively unifying evidentiary standards and emphasizing judges' prudence in deciding divorce cases. However, in practice, these provisions can also create barriers to access to justice for economically, socially, and psychologically vulnerable parties, particularly in proving separation and domestic violence. Therefore, the fulfillment of substantive justice through the implementation of SEMA is highly dependent on judges' sensitivity in understanding the factual realities of households and their ability to interpret norms progressively, flexibly, and contextually.